Realization of Low-Code Algorithm for Steel Energy Consumption Prediction - Ji, Wanzhou; Bian, Yunqi; Cai, Hongxia (IEEE International Conference on Computer Communication and the Internet (Online), 2024)
The steel industry is one of the world's highest energy consumption. It is important to improve its energy efficiency. Energy consumption prediction can help steel industry better plan and manage energy use. Based on a low-code development platform, multiple prediction algorithm models are used to predict the energy consumption. A low-code algorithmic platform support is provided for the steel industry to achieve energy saving and efficiency improvement.